Edukasi Literasi Digital untuk Mencegah Penyebaran Berita Hoax di Desa Pinang Banjar - Bambang Irawan; Vany Alia Putri; Monica Angelia; Rifky Oktri Romahdoni; Agung Prayoga; Muktiono (Jurnal Sinergi Sistem Informasi Pengabdian Masyarakat, 2026)
The continuous progress in information and communication technology has significantly increased the use of social media as a a central channel for sharing information, although it has also resulted in to the widespread dissemination of hoaxes that can lead to misinformation, social conflict, and declining public trust. This issue is largely driven by low levels of digital literacy, particularly in rural areas such as Pinang Banjar Village, where people still face difficulties in distinguishing between valid and false information. This research aims to investigate how digital literacy is implemented education in preventing the spread of hoaxes and improving public understanding. The method used is a community service approach through community outreach, learning sessions, and interactive engagement and the presentation of real-life hoax examples in visual form, including WhatsApp scams, fake financial aid, and fraudulent giveaways. The results indicate that this educational program effectively enhances the community’s ability to identify hoax characteristics, verify information, and encourages more selective and responsible behavior in using social media. In addition, awareness of digital threats, such as online fraud and suspicious links, has also increased. Therefore, digital literacy education contributes greatly to building a more critical and informed society, and it should be implemented continuously.